(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The novel “Magus” illustrates such postmodern techniques as intertextuality(“Robinson Crusoe” by Daniel Defoe and Twelfth Night "- a play, William Shakespeare’s comedy), existence and the extremes of human sufferings, historical events like: an apparition of the Reverend Robert Foulkes, executed in 1679 for murdering his unborn child; Conchis’ desertion of his trench-bound military unit during the First World War; a mythic masque depicting Apollo and Artemis; and finally, the execution of Greek villagers, where, during the German occupation, Conchis had, he implies, been mayor. In this article, The Magus is primarily classified as an origin story. Its main character, Nikolai Urfe, graduates from higher education, takes a teaching position in Greece, meets Maurice Konchis, and engages in immoral acts in emotional relationships.